Wideband coupler for butler matrix antenna beamforming - Sabri, Muataz Watheq Sabri (2015)
This work focuses on the design of a Wideband Branch Line Coupler (BLC) by using open circuits coupled lines technique. The design is implemented by adding four open circuits coupled lines to the structre of the conventional Branch Line Coupler. The coupler operates at 3.8 GHz with a wideband bandwidth of 1.66 GHz, in which the fractional bandwidth is 43.69%. Then the proposed design was implemented using CST microwave tool and the simulation results of the S-parameters obtained from CST microwave simulated achieving a coupling factor of -3d and 0 phase diffrence between the two output port at the frequency of 3.8 GHz , the fabrication process and the experiment results of the proposed prototype wideband BLC was discussed and compared. The simulated results, and the measured results similar with wider bandwidth of 1.62 GHz and fractional bandwidth of 42.63% with reducation size of 28.2%.